Drums of change : the story of Running Fawn - Oke, Janette, 1935- (Minneapolis, Minn. : Bethany House Publishers, 1996)
During the mid-19th century, white settlers in Alberta steal lands from Running Fawn's tribe and she must resign herself to living on the reservation.
A novel.
810
Accelerated Reader AR
Keywords: Indians of North America -- Alberta -- Fiction; Indian women -- Alberta -- Fiction; Alberta -- History -- Fiction; Christian fiction; Love stories; Historical fiction; Western stories